eReadiness and eCommerce success: developing and exploring an antecedent model in developing countries context - Molla-Adankew, Alemayehu (Department of Information Systems, 2019)
eCommerce is touted as offering developing countries unprecedented opportunities for economic growth and development. In addition, current wisdom maintains that developing countries' success in eCommerce will have an impact far beyond their borders in accelerating global productivity and facilitating global economy success. Therefore, understanding how eCommerce is accepted by businesses in developing countries and what affects its success are primary issues of interest for researchers, businesses, governments and development agencies. The literature on IT, eCommerce, eReadiness and eCommerce success in developing countries has been examined and critiqued. The result reveals the environmental determinism view as a dominant perspective in most of the existing works and the lack of a theoretically sound model to explain and understand eCommerce success in developing countries. Using a theoretically eclectic approach derived from organization science, information systems, competitiveness, innovation and institutional theories and based on an interactionism perspective, the study proposes a theoretical framework for eReadiness and eCommerce success with particular relevance to established businesses in developing countries. From the framework, a model relating nine organizational (awareness, commitment, governance and human resources, business resources and technological resources) and environmental (government, market forces and supporting industries) constructs of eReadiness and four facets of eCommerce success (adoption, development, deployment and benefits) is derived. An instrument to operationalize the model is developed and validated. The model is empirically tested based on data collected from a cross section of 150 South African businesses using multivariate statistical techniques. The result shows various blends of organizational and environmental eReadiness factors affecting the different facets of eCommerce success. The key finding refutes the environmental determinism perspective that dominates eCommerce discussion in developing countries and supports the interactionism perspective. It is concluded that if we are to understand the emergence and development of eCommerce in developing countries we must depart from the conventional wisdom of looking into environmental constraints only and pay attention to internal organizational capabilities and characteristics as well.